Hubungan Tingkat Ansietas Terhadap Quality of life Pada ODHA - Daramatasia, Wira; Kurniyanti, Mizam Ari (Journal of Islamic Medicine, 2021)
Background: HIV/AIDS is one of the worst pandemics, in addition to the physical impact psikososial that make fear. Increased anxiety can affect the quality of life in ODHA. Objectif : The research aims is to understand the anxiety in the quality of life of patients odha in peer support groups JCC+. Methods : This research using analytic observational with the approach of cross sectional. Respondents were 40 taken with purposive approach based on techniques of sampling from 367 responden that include in the criteria and ekslusi who join the KDS JCC. Quality of life ODHA assessed using a questioner WHOQOLHIV BREF, anxiety levels measured by the questionnaire zung self-rating anxiety scale ( ZSAS). Data analysis using spearman test to test relation between levels of anxiety with Qol with the level of significance 5 %.. Results: The results of research related to the quality of life based on 6 ODHA, domain to have enough physical domain category of 52,5 %, psychological domain have good category of 75 %, the domain independence have quite as much as 70 %, category domain have enough social category of 52,5 %, the domain ward having good category of 52,5 % religious and spiritual domain / having good category of 70 %. The anxiety on the majority of 85 odha % is categorized as a mild anxiety .There is a significant relation exists between the level of anxiety with a domain ODHA quality of life. Conclusion : The conclusion of a significant relation exists between the level of anxiety in the quality of life of the majority of 85 odha.tingkat anxiety on odha % is categorized as a mild anxiety .There is a significant relation exists between the level of anxiety with a domain odha quality of life (r1=-0,1258 , r2=-0,1144, r3=-0,0533, r4=-0,1258, r5=-0,1398, dan r6=-0,0609) .The conclusion of a significant relation exists between the level of anxiety by odha quality of life.